Multi-Criteria Analysis and Design Ideas of Green Façade Systems as Eco-Friendly Architectural Solutions - Kamińska, Patrycja; Michalak, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses current trends in designing green and eco-friendly façades of buildings of different functions in Poland and around the world. Information collected on completed façade projects, associated research and conclusions formulated on the basis thereof, indicate trends and possibilities for the use of contemporary material solutions and technologies in designing various forms of vertical "greenery" which support sustainable development of urban areas.
Keywords: green façade; innovation in architecture; urban greenery; concept; aesthetics; eco-friendly solution; modular system